A Review on the Antioxidant Activity of Select Philippine Fruitsand Wines - Babista, Kyle Nicole P. (Animo Repository, 2021)
Antioxidants are an abundant type of substance that is found in various fruits and wines. The literature on antioxidants has been growing consistently due to various reports on their health benefits. Hence, this study is a literature review of the antioxidant activity of local fruit and wines in the Philippines using various spectrophotometric techniques. Specifically, the researchers assessed the state of research on the antioxidant properties of local fruits and the effect of temperature and aging on the antioxidant activity of local wines. In gathering the related studies, the following keywords/phrases were used: “antioxidant activity of Philippine wines”,” spectrophotometry”, “Philippine fruit”, and “temperature and age of Philippine wines.” These were assessed using the Quality of Reporting of Meta-analyses (QUORUM) standard to measure its reliability. The results showed that there was a correlation between the temperature of both local fr s a considerable heterogeneity for the temperature of the fruits and wines towards the antioxidant (I2 = 34.64%; I2 = 40.00%). But the data for the age and wine were varied significantly since it accounted for a high heterogeneity (I2 = 82.69%). In conclusion, there was a mildly significant correlation between the temperature of both fruit and wines towards the antioxidant activity. However, the wine age did not affect its antioxidant activity.